BAD guidelines for SJS/TEN in children and young people, 2018. (1st July 2019) - McPherson, T.; Exton, L.S.; Biswas, S.; Creamer, D.; Dziewulski, P.; Newell, L.; Tabor, K.L.; Wali, G.N.; Walker, G.; Walker, R.; Walker, S.; Young, A.E.; et al.
Summary: Stevens–Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN) are urgent, serious immune reactions in which there is skin loss and severe ulcers in the mouth, eyes and genital areas. It affects about 5‐6 people per million under 18 years of age in the U.K. each year. It has a mortality of (causes death in) 5‐10% and re‐occurs in up to 18% of survivors. The British Association of Dermatologists led a group of relevant experts to examine the evidence in developing guidelines to aid diagnosis and management of SJS/TEN in children and young people. As with many rare conditions, there are few high‐quality trials comparing one treatment with another. Most of the evidence comes from patient examples reported in the medical literature (i.e. medical journals). The research reveals some important differences between children and adults in terms of the cause and outcomes of SJS/TEN. Infections are a more common cause in children and young people although medication can be the cause in all ages. Children are less likely to die from SJS/TEN than adults. Preventing long‐term complications is of key importance. Management in the early stages should ensure the identification of the cause, stopping any possible medications that might be the cause, and consideration of infection as the trigger. The best evidence for improved outcomes is good supportive care in the right clinical environment. This requires admission to appropriate specialist units with experience in managing skin loss, and a team of hospital specialists who can address all potential clinical complications. Longer‐term management involves supporting patients and their families with any resulting complications including those affecting the eyes, skin, lungs and psychological impact. The guidelines highlight that there is still much that is unknown about the best way to manage this potentially devastating reaction, and identifies the need for better routine data collection, diagnosis and standardised treatment, as well as a multi‐disciplinary (involving different types of healthcare workers) approach to management. Abstract : Linked Article: McPherson et al. Br J Dermatol 2019; 181 :37–54